The Summary of School Leaderships Theories According to Malaysia Perspectives - Jude James; Rosy Talin; Soon Singh Bikar Singh (Secholian Publication, 2022)
This study will look at English-language publications on school leadership, worldwide trends, and Malaysian research. The methodology includes a comprehensive review of journal articles and book chapters about school leadership research published in the English language. To find a potential gap in the current literature and advise a school leadership researcher on the best future research direction. According to the findings, existing leadership theories were all established and honed in Western contexts, raising concerns about their applicability for Malaysian circumstances. The findings show that more research utilizing a qualitative method is needed to tailor the theory to local situations. This study contributes to the inadequate information base on leadership in Malaysia and throws light on the evolution of educational systems by providing foundational knowledge and guidance for scholars and practitioners.